Healthcare usage and satisfaction among young adult gay men in New York city. Issue 4 (1st October 2020) - Griffin, Marybec; Cahill, Sean; Kapadia, Farzana; Halkitis, Perry N.
Abstract: Satisfaction greatly impacts decisions about where and how to access healthcare. This cross-sectional study uses data gathered from young adult gay men in New York City. Findings indicate that participants who experienced discrimination in a healthcare setting were less likely to prefer coordinated healthcare. Participants who disclosed their sexual orientation and were comfortable discussing sexual activity with their provider were more likely to agree that their healthcare needs were adequately addressed. The healthcare system does not fully address the healthcare needs of gay men. Preferences for coordination of care, nondisclosure of sexual orientation, and low levels of satisfaction with services further discourage healthcare usage among this population.